How Scaffolding Concept is Realised Through The Use of Feedback: A Sociocultural Perspective - Entusiastik, Entusiastik (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL; Vol 1 No 1 (2019): Education and Linguistics Knowledge Journal (Edulink), 2019)
The aim of this paper is to discuss how the metaphor of scaffolding is realised through the use of feedback in an ESL class in the US. In doing the analysis, I look at three types of feedback (self-feedback, peer feedback, and teacher feedback) and how each type help to shape the learning process in the learning context which is discussed. A number of experimental researches indicate that L2 learners would benefit from corrective feedback -regardless of the type of the feedback (Alfaajreh and Lantolf, 1994; Caroll and Swain, 1992). In the same vein, from this learning context, it can be concluded that each type of feedback can potentially serve as a mediation tool to scaffold students’ learning process.